War casualties and US presidential popularity: a comparison of the Korean, Vietnam and Iraq war - Geys, Benny (2010)
Abstract: "Conventional wisdom holds that war casualties depress incumbent popularity. We argue that the strength and even the direction of these effects is inherently context-dependent because the perception of casualties varies over time and space, affected by historical developments. While intuitive, this proposition has as yet not been directly addressed due to a lack of explicitly comparative analyses. Investigating US presidential popularity over the period 1948-2006, the present paper illustrates that intensity and occurrence of casualty effects on presidential popularity varies significantly across the three considered military conflicts (i.e. Korea, Vietnam, Iraq). Moreover, these differences can be credibly linked to historical developments." (author's abstract)